If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4/x-4=x
We move all terms to the left:
4/x-4-(x)=0
Domain of the equation: x!=0We add all the numbers together, and all the variables
x∈R
-1x+4/x-4=0
We multiply all the terms by the denominator
-1x*x-4*x+4=0
We add all the numbers together, and all the variables
-4x-1x*x+4=0
Wy multiply elements
-1x^2-4x+4=0
a = -1; b = -4; c = +4;
Δ = b2-4ac
Δ = -42-4·(-1)·4
Δ = 32
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{32}=\sqrt{16*2}=\sqrt{16}*\sqrt{2}=4\sqrt{2}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-4)-4\sqrt{2}}{2*-1}=\frac{4-4\sqrt{2}}{-2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-4)+4\sqrt{2}}{2*-1}=\frac{4+4\sqrt{2}}{-2} $
| -7=5(x+2)+8 | | -4x-36=4(3x+3) | | x-25=3(2x-5) | | -9x-9=-3x-63 | | -x-49=2(2x+3) | | x-28=5(4x+2) | | 4(3x-5)-1=-x+5 | | 5x+27=2(x+5)-10 | | 26=2(3x+4) | | 2x-7=2(2x-4)+5 | | -2x-173=124-11x | | 42=2(4x+5) | | 5x-34=2(5x+3) | | 16=4(2x-4) | | 13x–2(X-4)=8x+1 | | 3(5x-3)-1=-4x-29 | | -201-2x=10x+75 | | 3(x-4)-5=2x-26 | | (x-4)-5=2x-26 | | -14x-63=-9x+32 | | -95=6x | | 2x+19=49-3x | | 4=3h-h+2+10 | | 6x-88=13x+171 | | x=4/2x-4 | | 8x+29=−21+3x | | 16=7t-9 | | 24+24x=150+10x | | X(13-2x)=15 | | -25+2x=43+4x | | x+9=7x+9+6x | | 122y=4 |